2006
DOI: 10.1002/art.21736
|View full text |Cite
|
Sign up to set email alerts
|

A high‐resolution magnetic resonance imaging study of distal interphalangeal joint arthropathy in psoriatic arthritis and osteoarthritis: Are they the same?

Abstract: Objective. Distal interphalangeal (DIP) joint arthropathy is characteristic of both psoriatic arthritis (PsA) and osteoarthritis (OA), but the microanatomic basis for DIP joint localization is poorly understood. This study used high-resolution magnetic resonance imaging (MRI) to investigate the basis for hand disease localization in both conditions. Methods. Twenty patients matched for disease duration (10 with DIP joint PsA and 10 with DIP joint OA) and 10 normal control subjects were scanned with a 1.5T MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 14 publications
4
105
0
10
Order By: Relevance
“…In established cases of PsA, Jevtic and coworkers 16 using MRI described inflamed tissue in the hand joints extending far beyond the joint capsule, thickened collateral ligaments, and surrounding periarticular soft tissue, a pattern that is quite different from that observed in patients with RA. In another report, Tan, et al 17 showed, using MRI, prominent inflammatory changes in ligament, tendon, enthesis, and adjacent bone in the distal interphalangeal (DIP) joints of patients with PsA, and similar findings were observed in DIP joints among patients with osteoarthritis (OA) but to a lesser extent.…”
Section: Discussionmentioning
confidence: 77%
“…In established cases of PsA, Jevtic and coworkers 16 using MRI described inflamed tissue in the hand joints extending far beyond the joint capsule, thickened collateral ligaments, and surrounding periarticular soft tissue, a pattern that is quite different from that observed in patients with RA. In another report, Tan, et al 17 showed, using MRI, prominent inflammatory changes in ligament, tendon, enthesis, and adjacent bone in the distal interphalangeal (DIP) joints of patients with PsA, and similar findings were observed in DIP joints among patients with osteoarthritis (OA) but to a lesser extent.…”
Section: Discussionmentioning
confidence: 77%
“…The presence of microdamage in normal fingers at sites that are prone to erosion in RA supports the idea that synovitis could exacerbate joint damage and lead to clinically recognizable erosion (Figure 6b). This common biomechanical and functional thread also likely underscores the propensity for periarticular erosions in seronegative arthritis and even OA (15,16). Indeed, it was recognized more than 40 years ago that radiographic erosions tended to occur adjacent to the capsule, but this important anatomic observation went largely unnoticed (17).…”
Section: Discussionmentioning
confidence: 92%
“…Although patients with malignant spinal disease also often had RLs present and could be misdiagnosed as having SpA at a vertebral level, this was in fact a very uncommon misdiagnosis at the patient level, since the overall MRI picture was clearly indicative of malignant disease, due to spinal imaging features elsewhere ( Figure 5). We have previously noted that the MRI pattern of disease in the DIP joints in patients with PsA and those with OA is often similar (14). Recent findings from a non-fatsuppressed MRI study also suggested some potential overlap in chronic changes between SpA and spinal OA (42).…”
Section: Discussionmentioning
confidence: 93%
“…We have previously studied distal interphalangeal (DIP) joint disease in 2 distinctly different conditions, psoriatic arthritis (PsA) and osteoarthritis (OA), and found that MRI patterns of disease were difficult to differentiate, because the entheseal and bone-related changes were similar (14). We therefore assessed the pattern of MRI lesions typically noted in SpA across 3 major causes of chronic back pain, the clinically confirmed European Spondylarthropathy Study Group (ESSG) criteria for SpA (15), degenerative spinal arthritis (DA), and spinal malignancy/metastases, in comparison with a normal control group of subjects without back pain.…”
mentioning
confidence: 99%